Examining the relationship between psychological ability and quality of work life with job satisfaction of professors - Maleki, Asghar (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2021)
Background and purpose: This research was conducted with the aim of investigating the relationship between psychological ability and quality of work life with the job satisfaction of professors of Islamic Azad University, Bandar Abbas branch. Methodology: The method of this descriptive research is a correlational type. To determine the reliability of the questionnaire, Cronbach’s alpha method was used and it was calculated using SPSS software, which was 0.945 for Spritzer and Mishra’s psychological empowerment questionnaire and 0.945 for Walton’s quality of work life questionnaire. Reliability was 0.865 and for Herzberg’s job satisfaction questionnaire, reliability was 0.869. The statistical methods used in this research include descriptive statistics (percentage, frequency, mean and standard deviation) and inferential statistics (simple regression and multivariate regression). Findings: The results of the research showed that there is a positive and significant relationship between psychological ability and job satisfaction of Islamic Azad University professors, Bandar Abbas branch. Also, in examining the dimensions of psychological empowerment, the results showed that there is a relationship between competence, autonomy, influence, and trust with the job satisfaction of the professors of the Islamic Azad University of Bandar Abbas branch, and there is no relationship between meaningfulness and the job satisfaction of the professors of the Islamic Azad University of Bandar Abbas branch. Further, the results showed that there is a relationship between the quality of work life and job satisfaction of the professors of Bandar Abbas Islamic Azad University; Also, in the examination of the dimensions of the quality of work life, the results showed that there is no relationship between fair and appropriate compensation, safe and healthy working conditions, integration and social cohesion in the organization, the general atmosphere of life, social dependence of work life and the job satisfaction of the professors of the Islamic Azad University, Bandar Abbas branch. and there is no relationship between providing opportunities for growth and development security, human capabilities, legalism in the organization and the job satisfaction of the professors of Islamic Azad University, Bandar Abbas branch. Conclusion: Paying attention to the concepts of psychological empowerment and organizational behavior and helping to establish them in the educational system, in a meaningful relationship with job satisfaction, can be useful in improving the performance and efficiency of educational centers.